THE RELATIONSHIP BETWEEN ARM MUSCLE STRENGTH, ARM MUSCLE POWER AND BALANCE ON THE ACCURACY OF SQUAT POINTING RESULTS IN UNESA UKM PETANQUE ATHLETES - muhammadkosyim; Noortje Anita Kumaat; Heri Wahyudi; Dita Yuliastrid; Moh turi (Program Pascasarjana Universitas Negeri Jakarta, 2024)
This study aims to analyze the relationship between arm muscle strength, arm muscle power, and balance on the accuracy of squat pointing results in UNESA UKM petanque athletes. The main problem is the lack of specific research that explores the physical factors that influence the squat pointing technique in petanque. The research method used is a quantitative approach involving 20 athletes, 10 men and 10 women as samples. Data were collected through the measurement of arm muscle strength using a push-up test, arm muscle power through throwing a medicine ball, balance with the BESS method, and the accuracy of squat pointing. Data analysis was carried out by normality prerequisite test, as well as hypothesis test using Pearson correlation and multiple linear regression. The results showed that there was a significant relationship between arm muscle strength (r = -0.643, p < 0.01), arm muscle power (r = -0.732, p < 0.01), and balance (r = -0.590, p < 0.01) on the accuracy of squat pointing results. Conclusion The results of this study show that arm muscle strength, arm muscle power, and balance have a significant relationship with squat pointing accuracy in petanque athletes. Arm muscle power is the dominant factor that affects the accuracy of the throw. These findings show the importance of developing strength, power, and balance in the training program of petanque athletes to improve performance. Keywords: Arm Muscle Strength, Arm Muscle Power, Balance, Squat Pointing Accuracy, Petanque Athlete.